Speech Acts in the Written Language of Advertisements: McDonald’s Advertisements as a Case Study - El Bakri, Jawad (Fakultas Ilmu Budaya, Universitas Mulawarman, 2024)
The current study investigates the pragmatic notion of speech act in the written language of McDonald’s advertisements. Advertising has always been a subject of study which is approached by a wide range of disciplines such as psychology, sociology, anthropology, and linguistics. Advertising is a profitable industry in the modern world; however, the great deal of research which was conducted so far has not yet provided the answers for understanding the main determinants (factors) of effective advertising. This study is one among many attempts that have approached the pragmatic side of the written language of McDonald’s advertisements. Pragmatics, as the study of the so-called “the invisible meaning” and speech act as a key concept in the field, are considered to be an appropriate conceptual framework for conducting this study whose main objective is to determine the hidden and implicit meanings (speech acts) which are embedded in the gathered data (McDonald’s advertisements). Austin (1962) and Searle (1969, 1975) provide the conceptual framework for this study as it endeavors to interpret the written language of McDonald’s advertisements in terms of the most pervasive and frequent kinds of speech acts within the selected data. Speech act theory is important when it comes to explaining language because it provides a theoretical framework for understanding how language is used to perform various communicative acts such as making requests, giving advice, making promises…etc. The fact of grasping the various types of speech acts and the conditions under which they are considered to be felicitous (successful) can increase the author’s understanding of language use and its impact on those daily interactions among consumers and producers. The theoretical framework of speech act theory provides enough analytical tools for understanding how speech acts are used in the written language of McDonald’s advertisements. The researcher can make use of that theoretical framework to identify the most frequent and different acts and their effects on target consumers. The author qualitatively and quantitatively analyzes the gathered data in the sense that he uses content analysis, as a qualitative research tool, and quantifying the frequency of certain speech acts, as a quantitative research tool. This particular study has shown that directive, representative, and commissive speech acts tend to be much more frequent in the written language of McDonald’s advertisements. These speech acts are repeated at a different rate in the previously analyzed data. They are expressed in various categories such as requesting and inviting as directive speech acts, suggesting and concluding as representative speech acts, and promising as a commissive speech act. On the other hand, this research has also shown that expressive and declarative speech acts are minimized compared to the previously stated ones (representative, directive, and commissive acts). As a final statement, all of these types of speech acts are combined to increase the persuasive force of the language of McDonald’s written advertising discourse. The major limitation of this study is that only the written language of McDonald’s advertisements is investigated and other aspects such as sounds and visual presentations are not examined which are considered as well-defined opportunities that pave the way for further future research as far this research topic is concerned.